Pengaruh Diversifikasi Produk Kopi Banyuatis terhadap Profitabilitas di CV. Pusaka Bali Persada - SRIAYUNI, NYOMAN EMA; DARMAWAN, DWI PUTRA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p16, 2022)
The Effect of Banyuatis Coffee Product Diversification on Profitability  in CV Pusaka Bali Persada The Influence of Product Diversification of Banyuatis Coffee on Profitability of CV Pusaka Bali Persada Diversification is a company strategy to add new products that are related to existing products. Analysis of the factors affecting profitability is very important considering that many companies went bankrupt due to unhealthy finances. The purpose of this study is to determine the effect of Banyuatis coffee product diversification on the profitability of CV Pusaka Bali Persada. 10 product samples were obtained by using purposive sampling method. In addition, this study analyzes the company's financial statements from 2009–2018. CV. Pusaka Bali Persada diversifies its products in terms of packaging and types of coffee produced. Types of packaging are divided into three, namely packages of 40, 150 and 200 grams. The results of the analysis confirm that there is a positive and significant influence between diversification and company’s profitability. Based on SPSS data processing, the resulting F value (count) is 4.10 for 10 samples. With F count of 7.659, which means F (count) > F (tabel) (7,659> 4,10), the drop test on the H0 and H1 reports is accepted for the hypothesis. In conclusion, this research shows that there is a positive influence between product diversification and company’s profitability in the period 2009 to 2018.